Peran Administrasi Pertanahan dalam Pengendalian Pemanfaatan Kawasan Pertanian Lahan Basah Kabupaten Bogor: The Role of Land Administration in Controlling the Utilization of Wetland Agricultural Areas in Bogor Regency - Pramusintha Nugraha; Budi Mulyanto; Khursatul Munibah (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2021)
The area of irrigated rice fields during 2017-2018 has decreased by 19.84% in Indonesia and 30.10% in Bogor Regency. Wetland agricultural area of Bogor Regency Spatial Plan (RTRW) is intended for wetland food crops (lowland rice) which are cultivated intensively because their potential to provide an irrigation system thus urge to be protected. In certain conditions, land registration has impact on the conversion of agricultural land. This study aims to examine the relationship between land administration and the conversion of agricultural land. Interpretation of Google Earth imagery and field checks are methods for inventories of constructed land. The relationship between the variable y (built-up area) and the variable x (land administration) is modeled by Geographically Weighted Regression (GWR). Literature study of land administration regulations was carried out to understand the modeling results with the realities that occur in the field. The dynamics of land administration are greatest in the northern part of Central WP Bogor Regency, in the suburbs of South Tangerang City, and Depok City. The modeling produces a global value of R2 0.72 and local R2 0.44 to 0.86, meaning that land administration has the opportunity to become an instrument of control, by tightening the service requirements specified in the Regulation of the Head of the National Land Agency RI No. 1 Tahun 2010.